Karakteristik Pemecahan Masalah Matematika Siswa dalam Menyelesaikan Masalah Berpikir Aljabar ditinjau dari Jenjang Sekolah - Yohanes Hariaman Nada (Universitas Nusa Cendana, 2023)
Facts on the field show that there are still many students who have low abilities in solving mathematical problems. One of the factors that influence this is because students are not accustomed to practicing solving math problems in class. The questions given to students were only questions that put more emphasis on carrying out procedures and calculations. The research was carried out to obtain an overview of students' mathematical problem solving abilities. The research in question was carried out at the end of elementary school level and at the beginning of junior high school level. It is hoped that the results of this research can be used as material for consideration and input for improvements and changes in the learning process to improve students' mathematical problem solving abilities. This study uses a qualitative approach. While this type of research is a phenomenological study. Phenomenology is a study that describes what a person receives, feels and knows in his consciousness about the experiences he has experienced. And what emerges from that awareness is called a phenomenon. The subjects of this study were students of class VI elementary school and class VII junior high school. Based on the results of the research and discussion, it can be concluded that there are similarities and differences in the characteristics of problem solving abilities between students at the final level of the elementary school level and students at the initial level of the junior high school level.